Optimizing Wheat Yield, Water, and Nitrogen Use Efficiency With Water and Nitrogen Inputs in China: A Synthesis and Life Cycle Assessment - Li, Zhou; Cui, Song; Zhang, Qingping; Xu, Gang; Feng, Qisheng; Chen, Chao; Li, Yuan (Frontiers in Plant Science, 2022)
To meet the demand of the fast increasing population, enhancing the wheat (Triticum aestivum L.) yield and resource use efficiency by optimizing water and nitrogen (N) management can greatly improve agricultural sustainability and enhance regenerative farming in developing countries such as China. This study aimed to 1) assess the variability in wheat yield, water productivity (WPc), and N-use efficiency (NUEf) in response to water and N input based on identified optimal levels, and evaluate the environmental impact caused by the various inputs of water and fertilizer in different regions using life cycle assessment (LCA); 2) evaluate, model, and rank the impacts of environmental (e.g., soil nutrient status, climatic factors) and agronomic factors (e.g., water/N management practices) affecting wheat yield, WPc, and NUEf. Based on 126 studies conducted in China between 1996 and 2018, the current study used meta-analysis in combination with decision regression tree modelling and life cycle assessment. Results showed that irrigation and/or N addition increased the average yield and WPc by 40 and 15%, respectively, relative to control treatments with no irrigation or fertilizer application. The mean water and N saving potentials in China were estimated at 11 and 10%, respectively. Soil nutrient status (e.g., initial soil phosphorus and potassium) and soil organic carbon content affected the wheat yield, WPc, and NUEf more significantly than climatic factors (mean annual temperature) or water/N management practices. The structural equation-based modelling indicated that initial soil nutrient condition impacted productivity and resource-use-efficiency more at the below optimal water/N levels than above. The risk-factor-based feature ranking using decision tree-based regression indicated that site-specific environmental and soil condition was highly informative towards model construction but split-input of N or water had little impact on yield and input-use-efficiency. Life cycle assessment demonstrated that to further mitigate greenhouse gas emissions, water- or N-saving management should be promoted in China. Collectively, our research implies that long-term soil health/nutrient enhancement should be more beneficial for increasing yield and resource use efficiency in wheat production. Additionally, a greater focus should be placed on managing input quantity (e.g. water and N) rather than application frequency and method.